2021
DOI: 10.1177/00224294211006415
|View full text |Cite
|
Sign up to set email alerts
|

A National Analysis of Music Coursetaking, Social-Emotional Learning, and Academic Achievement Using Propensity Scores

Abstract: The purpose of this study was to examine the association between curricular high school music participation, academic achievement, and social-emotional learning. The analysis involved a “doubly robust” approach combining propensity score weighting and nested multiple regression using data from the nationally representative High School Longitudinal Study of 2009. Results of the study were mixed. Preliminary tests revealed many significant differences between the choral and instrumental students and the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 259 publications
(533 reference statements)
1
5
0
Order By: Relevance
“…These results are consistent with previous evidence that has demonstrated a similar relationship between art-based programs and academic performance 12 , 16 , 18 , 54 58 .…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with previous evidence that has demonstrated a similar relationship between art-based programs and academic performance 12 , 16 , 18 , 54 58 .…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, music education can support SEL in growing and understanding our emotions (Schellenberg & Mankarious, 2012), self-regulating our emotions (Sakka & Juslin, 2018), taking responsibility for our actions (Davidson & Good, 2002), developing empathy (Egermann & McAdams, 2013), and expressing ourselves (Gold et al, 2017). Shaw (2022) examined the association between high school music participation and social and emotional outcomes. Findings indicated that there were no strong associations and that there might be connections between enrollment in music courses (e.g., band, choir, orchestra) and social-emotional outcomes.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Researchers have found social outcomes of sharing, shared decision-making, cooperation, collaboration, independence, and student self-concept (Claire, 1993(Claire, /1994Ilari et al, 2019;Ritblatt et al, 2013;Shouldice, 2014;Trusty & Oliva, 1994;Wolf et al, 2019). Researchers also found that musical activities fostered feelings of belonging and identity, which contributed to students' social awareness, social responsibility, and team functioning (Abramo, 2011;Adderley et al, 2003;Allsup, 2003;Campbell, 1995;Coffman, 2002;Parker, 2010Parker, , 2018Shaw, 2022). Research focused on students' emotional development in music has identified outcomes, including growth in emotion regulation skills, fostering emotional connection, increased emotional awareness and sensitivity, stress reduction, and heightened enjoyment (Brown, 2020;Koops, 2018;Parker, 2010).…”
Section: Research On P-12 Students' Socioemotional Development From M...mentioning
confidence: 99%